Accuracy of advanced cancer patients' life expectancy estimates: The role of race and source of life expectancy information - Trevino, Kelly M. (Cancer, 2016)
BACKGROUND: To examine the source of advanced cancer patients' information about their prognosis and whether this source of information explains racial disparities in the accuracy of patients' life expectancy estimates (LEE). METHODS: Coping with Cancer is a prospective, longitudinal, multi-site study of terminally-ill cancer patients followed until death. In structured interviews, patients reported their LEE and the source of this estimate (i.e., medical provider, personal beliefs, religious beliefs, other). Accuracy of LEE was calculated by comparing patients' self-reported LEE to their actual survival. RESULTS: The sample for this analysis included 229 Black (n=31) and White (n=198) patients. Only 39.30% of the sample estimated their life expectancy within 12 months of actual survival. Black patients were more likely to have an inaccurate LEE than White patients. A minority of the sample (18.3%) reported that a medical provider was the source of their LEE; none (0%) of the Black patients based their LEE on a medical provider. Black race remained a significant predictor of an inaccurate LEE, even after controlling for sociodemographic characteristics and source of LEE. CONCLUSIONS: The majority of advanced cancer patients have an inaccurate understanding of their life expectancy. Black advanced cancer patients are more likely to have an inaccurate LEE than White patients. Medical providers are not the source of information for LEE for most advanced cancer patients, especially Black patients. The source of LEE does not explain racial differences in LEE accuracy. Additional research on mechanisms underlying racial differences in prognostic understanding is needed.